Menerapkan Nilai Moderasi Melalui Ajaran Agama untuk Mengembangkan Sikap dan Potensi Masyarakat Desa Kuala Beringin - Zuhri Fadli Ritonga; Dhiauddin Tanjung; Julreda Banu Br Sitorus; Elsa Valen Yunita; Nurul Hidayah Apriyanti Ritonga (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Religious moderation plays a very important role in social life to control human life and guide it to be good in the world. The purpose of this study is to achieve knowledge and outline of spiritual moderation and religious harmony in Kuala Beringin Village. This research method is in the form of field observations which are carried out directly through a word forum in Kuala Beringin Village and also a seminar conducted by KKN Group 144, North Labuhanbatu Regency. The results showed that religious moderation in the Kuala Beringin Village area has developed, this can be seen from the people who are still surviving by living their daily lives as usual. Viewed from the perspective of harmony between religious people, the people of Kuala Beringin Village strongly support harmony where mutual respect and respect for differences. Through KKN Activities we can realize a dignified society with work programs, especially in rural Kuala Beringin. The community tells the existing problems and then finds a way out with the participation of KKN participants, cooperation is established to achieve this success. As for the expected goals and targets of the work program. The people in Kuala Beringin village are arguably pluralism because they include many tribes, cultures, and religions. There are Javanese, Malay and Batak tribes that occupy the Kuala Beringin Village area. With the existence of religious pluralism in Kuala Beringin village, it makes values such as religious values, and cultures that can certainly form religious moderation such as, establishing religious teachings in interacting in the community so as to realize harmony between communities.